Cardiovascular Magnetic Resonance from Fetal to Adult Life-Indications and Challenges: A State-of-the-Art Review - Sara Moscatelli; Isabella Leo; Veronica Lisignoli; Siobhan Boyle; Chiara Bucciarelli-Ducci; Aurelio Secinaro; Claudia Montanaro (MDPI AG, 2023)
Cardiovascular magnetic resonance (CMR) imaging offers a comprehensive, non-invasive, and radiation-free imaging modality, which provides a highly accurate and reproducible assessment of cardiac morphology and functions across a wide spectrum of cardiac conditions spanning from fetal to adult life. It minimises risks to the patient, particularly the risks associated with exposure to ionising radiation and the risk of complications from more invasive haemodynamic assessments. CMR utilises high spatial resolution and provides a detailed assessment of intracardiac and extracardiac anatomy, ventricular and valvular function, and flow haemodynamic and tissue characterisation, which aid in the diagnosis, and, hence, with the management of patients with cardiac disease. This article aims to discuss the role of CMR and the indications for its use throughout the different stages of life, from fetal to adult life.